Analogize study to the social personality for Iraqi Basket ball player according to play positions - Abedulkareem, Hilal (Journal of Physical Education, 2015)
No doubt the social and psychological effects and problems has a big in flounce to athletes performance. So its must be under watching and control. The reasons of low slandered may be not physical of technical but may be psychological for that psychological studies must available to support player self-control abilities. The lake of this studies means big problem must saluted. The research goals to know the adult basketball player personality according to play positions. The sample contents 45 players. Represents 10% from the holl society of the clubs which taking part in the league who real participated. There is many conclusions in this study summarized by a differences in the player social variables personality standard according to game positions, also a contradiction answers appeared may be joined by the double socialism state which the player grown up with in them life. There is many recommendation suggested by the researcher such as to get more consideration to the psychological preparation and psychological skills, watching and take care of the player psychological and social life and rush up the study